STUDI KOMPARATIF PENGATURAN TINDAK PIDANA PENGHINAAN TERHADAP PEJABAT NEGARA MENURUT KUHP DAN UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Natasha Octarifana; Lola Yustrisia; Riki Zulfiko (Ensiklopedia of Journal, 2023)
Insulting state officials is a very immoral act personally, if it is connected with an activity that basically attacks a person's personality then it becomes something that is prohibited, but it becomes a frightening specter for the community that legal certainty is finally being questioned. The formulation of the problem in this study is that the first is how to regulate the criminal act of insulting a state official according to the criminal code, then how to regulate the law on the criminal act of insulting a state official according to the UTE Law. This research is analytical descriptive in nature, meaning that this research aims to provide data about a situation or social phenomena that develop in the midst of society according to facts and without engineering. The approach method used in this study is a normative juridical method, namely the collection of material or research materials aimed at written documents. The results of this research are that in the principle of a democratic state, the relations between the people and the state leaders are interrelated, because there is a check and balance mechanism as a representation of the strengthening of the state in a vertical form. Therefore, any form of lex specialis protection for state officials cannot be justified in a country that adheres to democratic presidential principles. On the other hand, because there has been regulation regarding the insult article in general, therefore the content built into the insult article against state officials is more inclined to create a dictatorship of the ruler in exercising his power. That the life of citizens should have something that guarantees legal certainty. The application of the latest criminal law is a context that has no correlation with the current situation and further advanced conditions that insult state officials through the ITE Law, basically historically the law was used to provide legal certainty for electronic transactions.